Factors influencing the usage of e-procurement among contractor companies in Malaysia / Norzaidi Mohd Daud, Nurliyana Mohammad, Arlina Erwany Azmi, and Intan Salwani Mohamed - Mohd Daud, Norzaidi; Mohammad, Nurliyana; Azmi, Arlina Erwany; Mohamed, Intan Salwani (Faculty of Business Management, 2013)
This paper is concerned with the factors influencing the usage of e-procurement among contractors companies in Klang Valley, Malaysia. The area of interests involved are; Perceived Ease of Use, Perceived Usefulness, Attitudes towards using e-procurement, and Intention to use e-procurement. 178 questionnaires were administered among several contractors companies registered under Construction Industry Development Board (CIDB). Findings have shown that intention to use e-procurement supported the hypotheses thus it is a factor that influence the usage of e-procurement. Further discussions and recommendations are proposed in order to improve the underlying problems. Keywords: E-procurement, contractor companies, usage, Malaysia